Édouard Manet. Text by Pierre Courthion. [Milton S. Fox, editor] - Manet, Édouard, 1832-1883. (The Library of great painters., 1962)
Contains forty color plates, supplemented by black-and-white reproductions with text and commentary on Manet's life and his works.